Characterization of Chlorine Fixation in Alkaline Metal-Modified Cu-Based Oxygen Carriers for Biomass Chemical Looping Combustion - Dezhe WANG; Yingjie MI; Haodong HUANG; Andong FU; Jinchen MA; Haibo ZHAO (能源环境保护)
The presence of chlorine (Cl) in biomass or pulverized coal poses a significant challenge in chemical looping combustion (CLC), as it can corrode both oxygen carriers and the boiler′s heat exchange equipment. Despite this, there is a notable lack of research focused on hydrochloric acid (HCl) in CLC processes. This study explores the development of a composite oxygen carrier aimed at enhancing chlorine fixation and corrosion resistance. To achieve this, two adsorbents, Ca-based and Ba-based, were selected. The composite oxygen carrier was synthesized using the sol-gel method, and a batch fluidized bed served as the experimental setup for biomass CLC experiments. The study investigated the effects of Ca and Ba doping on the combustion characteristics and chlorine bonding of Cu-based oxygen carriers. The results indicate that alkaline earth metals in Ca-Cu and Ba-Cu formulations preferentially form stable chlorides with HCl, enhancing the lattice oxygen activity of the carriers and promoting gas-solid reactions for chlorine capture. Notably, the peak CO2 production and peak height for Ca-Cu and Ba-Cu carriers were significantly higher than those for standard Cu oxygen carriers. Additionally, Ca/Ba doping improved the gasification of biomass coke, with no detectable levels of H2 and CH4 during the reduction stage, suggesting more complete conversion of these gases by oxygen carriers. The peak CO concentrations were measured at 0.08%, 0.07%, and 0.06% for Ca-Cu, Ba-Cu, and Cu carriers, indicating enhanced CO conversion efficiency. Further experiments assessed the impact of temperature and oxygen-fuel ratio on combustion and dechlorination performance. Increasing the temperature from 800 ℃ to 900 ℃ resulted in a combustion efficiency rise for the Cu oxygen carrier from 87.0% ± 0.5% to 94.7% ± 0.4%, representing a maximum increase of 8.6%. Conversely, the combustion efficiency of the Ca oxygen carrier decreased slightly from 95.6% ± 0.6% to 95.2% ± 0.1%. In contrast, the Ba oxygen carrier showed a significant improvement, increasing from 88.0% ± 1.6% to 94.7% ± 0.4%, with a maximum increase of 8.7%. In biomass CLC, Ca-Cu oxygen carriers demonstrated superior temperature stability, while the combustion efficiency of Ba-Cu carriers was significantly affected by temperature changes. When the oxygen-fuel ratio was raised from 1.5 to 2.0, the chlorine fixation efficiency for Cu carriers increased from 84.3% ± 6.3% to 96.3% ± 1.2%. Both Ca- and Ba-based oxygen carriers maintained 100% chlorine fixation efficiency, suggesting that lower oxygen-fuel ratios could be utilized in biomass dechlorination processes, thereby reducing carbon capture operating costs. Moreover, doping with Ca and Ba increased the specific surface area and pore volume of the oxygen carriers, increasing the contact area with biomass and thereby stabilizing their performance in CLC. This study helps to understand the chlorine fixation characteristics of alkaline earth metals, promoting the development and application of chlorine-resistant carriers.